2009
DOI: 10.1002/rcm.4309
|View full text |Cite
|
Sign up to set email alerts
|

Control of origin of larch wood: discrimination between European (Austrian) and Siberian origin by stable isotope analysis

Abstract: Most of the coniferous wood of non-European origin that is imported into the European Union (EU) has to be inspected phytosanitarily, to prevent the introduction and spread of harmful pests in EU territory. Wood importers have been caught declaring Siberian larch wood as being of European origin to save the costs of the inspection. Therefore, an unequivocal method has to be developed in addition to the traditional analysis of the tree ring density to identify incorrect declarations of larch wood origin. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Black line is the relationship for all points. All data were obtained from a review of current literature (Epstein et al, 1977;Buhay and Edwards, 1995;Saurer et al, 1998;Anderson et al, 1998;Saurer et al, 2000;Robertson et al, 2001;Waterhouse et al, 2002;Evans and Schrag, 2004;Shu et al, 2005;Welker et al, 2005;Ballantyne et al, 2006;Wright and Leavitt, 2006;Holzkämper et al, 2008;Norström et al, 2008;Richter et al, 2008b;Sidorova et al, 2008;Voltas et al, 2008;Battapaglia et al, 2009;Hilasvouri et al, 2009;Horacek et our site on Bylot Island, based upon two modern larch trees, one from the Yukon and one from Ottawa (Eq. (6)):…”
Section: Methodsmentioning
confidence: 99%
“…Black line is the relationship for all points. All data were obtained from a review of current literature (Epstein et al, 1977;Buhay and Edwards, 1995;Saurer et al, 1998;Anderson et al, 1998;Saurer et al, 2000;Robertson et al, 2001;Waterhouse et al, 2002;Evans and Schrag, 2004;Shu et al, 2005;Welker et al, 2005;Ballantyne et al, 2006;Wright and Leavitt, 2006;Holzkämper et al, 2008;Norström et al, 2008;Richter et al, 2008b;Sidorova et al, 2008;Voltas et al, 2008;Battapaglia et al, 2009;Hilasvouri et al, 2009;Horacek et our site on Bylot Island, based upon two modern larch trees, one from the Yukon and one from Ottawa (Eq. (6)):…”
Section: Methodsmentioning
confidence: 99%
“…(1) Traditional wood identification relies on diagnostic anatomical features observed by a trained expert, and this technology cannot identify wood samples to the species level because related species often have similar wood structure (Santos et al 2013;Yu et al 2016). (2) Phytochemical analysis (Mcclure et al 2015), near infrared spectroscopy (Pastore et al 2011;Bergo et al 2016), real time time-of-flight mass spectrometry (Cody et al 2012) for wood identification and isotopic analysis (Horacek et al 2009;Kagawa and Leavitt 2010;Krüger et al 2014) to determine provenance are growing but as-yet not widely deployable technologies. With progress in biotechnology, especially the application of DNA molecular marker technology in forensic medicine and archeology (Gould et al 2010;Gismondi et al 2012;Eurlings et al 2013;Phong et al 2014;Gismondi et al 2015Gismondi et al , 2016, another possible channel for reliably identifying wood and wood products and tracing their geographical origins is open (Nithaniyal et al 2014;Schroeder et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some initial results from attempts to identify the geographical origin of wood using tree-ring δ 13 C in the south-western United States have been reported by Kagawa and Leavitt [ 10 ]. Horacek et al [ 27 ] used the δ 13 C and δ 18 O values of bulk wood to discriminate between Siberian larch and European larch, while a study by Keppler et al [ 28 ] found the δ 2 H values of the lignin methoxyl groups to correlate strongly with the OIPC (Online Isotope Precipitation Calculator; accessible at http://waterisotopes.org/ ) δ 2 H values of meteoric water. Despite these recent preliminary studies, a comprehensive method for identifying the geographic origin of forest trees has not yet been found.…”
Section: Introductionmentioning
confidence: 99%